Elucidating the difference in the kinetics of antibody titres of infants in Belgium and Vietnam. Issue 45 (21st October 2020) - Tran, Thao Mai Phuong; Maertens, Kirsten; Hoang, Ha Thi Thu; Van Damme, Pierre; Leuridan, Elke; Hens, Niel
Abstract: Serological results obtained in a single laboratory from twin-studies on maternal immunisation, in Vietnam and Belgium offer the opportunity to compare antibody kinetics in infants before and after infant vaccination in the presence of vaccine-induced maternal antibodies. Nonlinear mixed-effects models (NLMMs) making use of a hypothesised dynamic evolution that captures the change in antibody titres over time, were employed to model anti-PT and anti-Prn antibody dynamics. Our proposed modelling approach provided useful insight into understanding the differences in the infants' antibody kinetics in both countries since NLMMs offer the possibility of pooling all data in one analysis and incorporate relevant covariates of interest. In both controlled cohort studies, pregnant women were vaccinated with a tetanus, diphtheria, acellular pertussis (Tdap) vaccine (Boostrix®, Belgium; Adacel®, Vietnam), and children were followed before and after primary vaccination, and before and after booster vaccination (Infanrix hexa®). From our models, both anti-PRN and anti-PT antibody titres at birth of Vietnamese infants were significantly lower than those of Belgian infants born to vaccinated women groups. Even though the antibody titres in the cord at birth of Belgian infants were also higher than those of Vietnamese infants born to the control women groups, the difference was not significant. The significant difference between infants born to vaccinated women in the two countries was likely due to the use of different vaccine brands in pregnant women and the different vaccination histories of women in these two countries. Our analyses also suggested that the blunting effect was present during the primary immunisation but went away afterward for anti-PT data. In contrast, for anti-PRN antibodies, the blunting effect persisted after the primary vaccination and possibly went away after the booster dose. Countries should be aware of the regional situation in view of recommending maternal immunization.